An R2R3-MYB transcription factor VyMYB24, isolated from wild grape Vitis yanshanesis J. X. Chen., regulates the plant development and confers the tolerance to drought - Zhu, Ziguo; Quan, Ran; Chen, Guangxia; Yu, Guanghui; Li, Xiujie; Han, Zhen; Xu, Wenwen; Li, Guirong; Shi, Jiangli; Li, Bo (Frontiers in Plant Science, 2022)
In grapevines, the MYB transcription factors play an important regulatory role in the phenylpropanoid pathway including proanthocyanidin, anthocyanin, and flavonoid biosynthesis. However, the role of MYB in abiotic stresses is not clear. In this study, an R2R3-MYB transcription factor, VyMYB24, was isolated from a high drought-tolerant Chinese wild Vitis species V. yanshanesis. Our findings demonstrated that it was involved in plant development and drought tolerance. VyMYB24 is a nuclear protein and is significantly induced by drought stress. When over-expressed in tobacco, VyMYB24 caused plant dwarfing including plant height, leaf area, flower size, and seed weight. The GA1+3 content in transgenic plants was reduced significantly, and spraying exogenous gibberellin could recover the dwarf phenotype of VyMYB24 transgenic plants, suggesting that VyMYB24 might inhibit plant development by the regulation of gibberellin (GA) metabolism. Under drought stress, the VyMYB24 transgenic plants improved their tolerance to drought with a lower wilting rate, lower relative electrical conductivity, and stronger roots. Compared to wild-type tobacco plants, VyMYB24 transgenic plants accumulated less reactive oxygen, accompanied by increased antioxidant enzyme activity and upregulated gene expression levels of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) genes. In addition, transgenic plants accumulated more proline, and their related synthetic genes NtP5CR and NtP5CS genes were significantly upregulated when exposed to drought. Besides, abiotic stress-responsive genes, NtDREB, NtERD10C, NtERD10D, and NtLEA5, were upregulated significantly in VyMYB24 transgenic plants. These results indicate that VyMYB24 plays a positive regulatory role in response to drought stress and also regulates plant development, which provides new evidence to further explore the molecular mechanism of drought stress of the MYB gene family.